MANAJEMEN BANDWIDTH MENGGUNAKAN METODE HIERARCHICAL TOKEN BUCKET (HTB) DENGAN PENAMBAHAN BUCKET SIZE USAHA AJ COMP - Andhika, Maulana Hafidz; Arip Solehudin; Didi Juardi; Garno (Elkom : Jurnal Elektronika dan Komputer, 2022)
The internet is currently very much needed because of the increasing use of many people depending on the internet because this information technology is very fast.In this case, it has a very big impact, the need for a very efficient internet service provider is needed. One of the technologies that is becoming a trend in computer networks is wireless computer networks (wireless local area network/WLAN) This technology is the development of local computer network technology (local area network) which allows efficiency in the implementation and development of computer networks that can increase user mobility with computer network technology using cable media. Bandwidth management is a way to manage the internet network for even distribution of bandwidth usage even though many network users use it. Hierarchical token bucket (HTB) one method to do a bandwidth management in this HTB